Pengaruh Kepemimpinan Kepala Sekolah, Kompetensi Guru dan Motivasi Kerja Guru terhadap Budaya Organisasi serta Implikasinya pada Kinerja Guru - H. M. Masruri (Kontigensi : Jurnal Ilmiah Manajemen, 2014)
The purpose of this study was to analyze analyze and assess the effect of school leadership, teacher competence and teacher morivasi of organizational culture and performance of teachers. The research method used is descriptive and verification with a sample of 210 teachers of SMK Negeri. Data were analyzed using analysis techniques Path (Path Analysis). These results indicate that: there is a significant influence of the Leadership Principal of organizational culture influence SMK with the amount of 16,10 percent. Where the principal leadership variables have the greatest influence both. Kemudin significant influence of teacher competence on organizational culture influence SMK magnitude of 3,50 percent. Where the competence variables have the greatest influence. There is a significant influence on the motivation of teachers of organizational culture influence SMK with the amount of 13,70 percent. Where the motivation variable gives the smallest influence. And there is a significant influence on the leadership of the principal, teacher competence and motivation of teachers, the organizational culture SMK, with the magnitude of the effect of 74,30 percent, while the influence of other variables amounting to 25,70 percent. As well as the significant influence of organizational culture SMK on teacher performance with the amount of influence by 79,20 percent, while the influence of other variables amounting to 20.80 percent.